Postcranial skeletal anatomy of the holotype and referred specimens of Buitreraptor gonzalezorum Makovicky, Apesteguía and Agnolín 2005 (Theropoda, Dromaeosauridae), from the Late Cretaceous of Patagonia - Gianechini, Federico A. (PeerJ, 2018)
Here we provide a detailed description of the postcranial skeleton of the holotype and referred specimens of Buitreraptor gonzalezorum. This taxon was recovered as an unenlagiine dromaeosaurid in several recent phylogenetic studies and is the best represented Gondwanan dromaeosaurid discovered to date. It was preliminarily described in a brief article, but a detailed account of its osteology is emerging in recent works. The holotype is the most complete specimen yet found, so an exhaustive description of it provides much valuable anatomical information. The holotype and referred specimens preserve the axial skeleton, pectoral and pelvic girdles, and both fore- and hindlimbs. Diagnostic postcranial characters of this taxon include: anterior cervical centra exceeding the posterior limit of neural arch; eighth and ninth cervical vertebral centra with lateroventral tubercles; pneumatic foramina only in anteriormost dorsals; middle and posterior caudal centra with a complex of shallow ridges on lateral surfaces; pneumatic furcula with two pneumatic foramina on the ventral surface; scapular blade transversely expanded at mid-length; well-projected flexor process on distal end of the humerus; dorsal rim of the ilium laterally everted; and concave dorsal rim of the postacetabular iliac blade. A paleohistological study of limb bones shows that the holotype represents an earlier ontogenetic stage than one of the referred specimens (MPCA 238), which correlates with the fusion of the last sacral vertebra to the rest of the sacrum in MPCA 238. A revised phylogenetic analysis recovered Buitreraptor as an unenlagiine dromaeosaurid, in agreement with previous works. The phylogenetic implications of the unenlagiine synapomorphies and other characters, such as the specialized pedal digit II and the distal ginglymus on metatarsal II, are discussed within the evolutionary framework of Paraves.